Minimally invasive versus open right hepatectomy: comparative study with propensity score matching analysis - Duarte, Vinícius Campos (BMC Surg, 2020)
BACKGROUND: Minimally invasive liver resections (MILRs) have been increasingly performed in recent years. However, the majority of MILRs are actually minor or limited resections of peripheral lesions. Due to the technical complexity major hepatectomies remain challenging for minimally invasive surgery. The aim of this study was to compare the short and long-term outcomes of patients undergoing minimally invasive right hepatectomies (MIRHs) with contemporary patients undergoing open right hepatectomies (ORHs) METHODS: Consecutive patients submitted to anatomic right hepatectomies between January 2013 and December 2018 in two tertiary referral centers were studied. Study groups were compared on an intention-to-treat basis after propensity score matching (PSM). Overall survival (OS) analyses were performed for the entire cohort and specific etiologies subgroups RESULTS: During study period 178 right hepatectomies were performed. After matching, 37 patients were included in MIRH group and 60 in ORH group. The groups were homogenous for all baseline characteristics. MIRHs had significant lower blood loss (400 ml vs. 500 ml, P = 0.01), lower rate of minor complications (13.5% vs. 35%, P = 0.03) and larger resection margins (10 mm vs. 5 mm, P = 0.03) when compared to ORHs. Additionally, a non-significant decrease in hospital stay (ORH 9 days vs. MIRH 7 days, P = 0.09) was observed. No differences regarding the use of Pringle’s maneuver, operative time, overall morbidity or perioperative mortality were observed. OS was similar between the groups (P = 0.13). Similarly, no difference in OS was found in subgroups of patients with primary liver tumors (P = 0.09) and liver metastasis (P = 0.80). CONCLUSIONS: MIRHs are feasible and safe in experienced hands. Minimally invasive approach was associated with less blood loss, a significant reduction in minor perioperative complications, and did not negatively affect long-term outcomes.